Digit ratio (2D:4D) in a Chinese population with schizophrenia. (July 2016) - Qian, Wenli; Huo, Zhenghao; Lu, Hong; Sheng, Youjing; Geng, Zhi; Ma, Zhanbing
Abstract: Background: Prenatal gonadal hormones may play a major role in pathogenesis of schizophrenia. It has been reported that second to fourth digit ratio (2D:4D) was influenced by the levels of exposure to prenatal testosterone and estrogen. So, 2D:4D may help to predict the disease susceptibility to schizophrenia. Aims: The aim of this study was to investigate the relationship between the digit ratio (2D:4D) and schizophrenia in Chinese population. Methods: We recruited 178 schizophrenics (males: 76; females: 102) and 365 controls (males: 218; females: 147) in this study. Photocopies of both hands were collected and left hand, right hand, mean hand and left minus right hand (DL-R ) 2D:4D were analyzed. Results: The right and mean hand 2D:4D ratios were significantly higher in schizophrenics compared to that of controls in both males and females. The left hand 2D:4D ratio in female schizophrenics was also significantly higher than in controls. Compared to controls, the DL-R 2D:4D in male schizophrenics was obviously higher. There was a weakly (but not significantly) negative correlation between the mean hand 2D:4D ratio and the age of onset. Conclusions: The 2D:4D ratio may correlate with the schizophrenia in Chinese population, and it may be an indicator of schizophrenia. Highlights: We investigated the relationship between 2D:4D ratio and schizophrenia in a Chinese population. Schizophrenics have significantly higher right and mean hand 2D:4D ratios than controls. There was a weakly (not significantly) negative correlation between the mean hand 2D:4D and the onset age in male schizophrenics.